2003
DOI: 10.1016/s1470-0328(03)02343-7
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for stress, urge or mixed urinary incontinence in Italy

Abstract: on behalf of VIVA Study Group A list of VIVA members is provided on page 932Objective To assess risk factors for different type of urinary incontinence -stress, urge or mixed -and overactive bladder without urinary incontinence. Design Case -control study. Setting Gynaecology clinics.Population Women attending first level gynaecological centres.Methods Cases were 1062 women with urinary incontinence or overactive bladder aged 40 years or more (mean age 62.3 years, range 40 -88) consecutively observed in first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
51
3
6

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(68 citation statements)
references
References 14 publications
8
51
3
6
Order By: Relevance
“…In accordance with previous studies [5,[9][10][11][12][13][14], hysterectomy in this study showed a particular increase in the risk of developing UI. However, there was no difference in the prevalence of UI regarding the route the surgery took, i.e., either transvaginally or transabdominally.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In accordance with previous studies [5,[9][10][11][12][13][14], hysterectomy in this study showed a particular increase in the risk of developing UI. However, there was no difference in the prevalence of UI regarding the route the surgery took, i.e., either transvaginally or transabdominally.…”
Section: Discussionsupporting
confidence: 93%
“…Most epidemiological studies for risk factors of UI also reveal that increasing BMI is positively related to the prevalence of UI [2,[9][10][11][12][15][16][17]. Nevertheless, there were some studies that showed that the increased risk for incontinence was not due to differences in weight [5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…Data were collected by a questionnaire containing two sets. In the first part, data about UI and OVB were obtained by using UDI-6 and the following questions [2,7,8].…”
Section: Methodsmentioning
confidence: 99%
“…and "Have you had any urgency symptoms? ", but (2) answering 'no' to the question "Have you had any involuntary urinary loss during the last month? ".…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation